The art of Sukumar Bose : reflections on South and Southeast Asia - Purushothaman, Venka (Singapore : Institute of Southeast Asian Studies, 2013)
To commemorate the centenary of artist Sukumar Bose (1912-1986), this book attempts to take an incisive look at the artist, his works and the context of his art production in South and Southeast Asia. Bose's art varied from the traditional to the decorative and ornamental, with a hint of the Oriental flavour. His work demonstrated traces of the Bengal School styles of Abanindranath Tagore and AR Chugtai. Be it figurative, landscape or abstract, Bose's art synthesized the decorative elements of Indo-Persian miniatures with Chinese and Japanese techniques.
Cover, Title,The art of Sukumar Bose : reflections on South and Southeast Asia--Preface, Introduction, TOC,Table of Contents--References, Appendix, Index,Catalogue of images in chronological order of production.
Keywords: Bose, Sukumar, -- 1912-1986 -- Criticism and interpretation; Artists -- India; Art, Indic -- India -- 20th century; Art, Indic -- Southeastsia -- 20th century